THE CORRELATION BETWEEN STUDENTS’ EXTRAVERSION PERSONALITY AND THEIR WRITING SKILL AT MUHAMMADIYAH UNIVERSITY OF MAKASSAR (A DESCRIPTIVE STUDY) - Ismail Sangkala (Universitas Muhammadiyah Makassar, 2012)
The Research Question is “Is there any Correlation between Students’ Extraversion Personality and their writing skill of the Muhammadiyah University of Makassar? “The Researcher used Descriptive Study; the aims of the thus research are to find out the correlation between students’ Extraversion Personality and their writing skill. The result of the students’ writing test had increased in scores. The mean score of students writing skill is 32, 72 and mean score of personality test is 59, 41. The successful of minimal criteria (KKM) was 70 there were students got very good in writing skill and Personality test students’ got balance.Keywords: Correlation, Students’ extraversion, Personality, Writing Skill